Sodium butyrate pretreatment mitigates lipopolysaccharide-induced inflammation through the TLR4/NF-κB signaling pathway in bovine embryo trachea cells. Issue 7 (12th December 2022) - Liu, Jing; Chang, Guangjun; Huang, Jie; Ma, Nana; Wang, Yan; Roy, Animesh Chandra; Shen, Xiangzhen
Abstract: The present study investigated the anti-inflammatory effects and potential mechanisms of sodium butyrate (SB) in bovine embryo tracheal cells (EBTr) stimulated with lipopolysaccharide (LPS). EBTr were exposed to either 1 mmol/L SB for 18 h for the SB group (SB) or to 0.4 μg/mL LPS for 6 h for the LPS group (LPS). PBS was added to EBTr for a control group (CON). EBTr were pretreated with SB for 18 h followed by 6 h of LPS stimulation for the LSB group (LSB). Results showed that with LPS stimulation, the gene expression of TLR4, NF-κB, IL6, and IL8, as well as cytokine production of IL6 and TNF-α, were significantly increased compared with the CON group. In contrast, protein expression of IL10 was decreased. However, these inflammatory effects induced by LPS were reversed in the LSB group. Compared with the CON group, protein expression of TLR4, phospho-NF-κB p65, phospho-IκBα, and IL1α were increased in the LPS group and these were decreased in the LSB group. Similarly, increased nuclear translocation of phospho-NF-κB p65 in the LPS group was suppressed with SB pretreatment. In conclusion, SB can reduce inflammation induced by LPS in EBTr, and this positive effect is mediated through the TLR4 and NF-κB signaling pathway.